Treasures of Egypt : a legacy in photographs from the pyramids to Cleopatra - Hiebert, Fredrik T.; Williams, Ann R. (National Geographic, 2022)
"The images in this breathtaking volume celebrate the vibrant beauty and rich cultural heritage of Egypt on the 100th anniversary of the discovery of King Tut's tomb"--